(untitled) (Eurasian Journal of Philology Science and Education, 2022)
At present, the study of the language, literature, religion, worldview, common values, spiritual heritage, worldview of the Turkic peoples is gaining momentum. Undoubtedly, the recognition of the origins of the Turkic peoples, who have the same origins and centuries of history, is, in the end, the recognition of the past and nature of each nation belonging to this ethnic group. From this point of view, it is desirable to identify the similarities and differences between the Kazakh and Turkic languages, to turn it into a branch of science. The article is one of the most fruitful and extensive areas of vocabulary of the Kazakh and Turkish languages - the only scientific and practical tool for closer acquaintance with plant names by comparing bilingual materials, linguistic data, mastering the thematic content and theoretical basis. The ethnolinguistic aspect of the Kazakh and Turkish peoples’ views on plants came to light as a result of this goal. In our article, the motives for the origin of plant names in the two vernacular languages, their names, which are similar to other phenomena, are compared, their commonalities and differences, national cognition in tokens related to cultivated plants are described and identified. The linguistic nature of plant names has been studied ethnolinguistically. Attention was paid to the nature of the names in the classification of plants. Plant names in the Kazakh and Turkish languages are semantically grouped. An overview of the study of plant names in linguistics, ethnolinguistic research. An analysis of the common denominators of phytonims in the Kazakh and Turkish languages was made, which were considered in the ethnolinguistic aspect. The main purpose of the study is to study the mythology of the Turkic peoples, to show their understanding of plants, to compare proverbs and sayings. Key words: ethnolinguistics, national knowledge, plant names, motivation